2010
DOI: 10.1186/2040-2392-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age increases the risk for autism in an Iranian population sample

Abstract: BackgroundAutism is a neurodevelopmental disorder which is known to have a strong genetic component and is most likely oligogenic. However, the necessary role of environmental factors has been well documented. Prior research suggests that parental characteristics, such as age and level of education, may be associated with a risk of autism. Parental age has been shown to be associated with many disorders, such as schizophrenia, childhood cancer and fetal death. However, results from studies of parental age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
4
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 55 publications
5
55
4
4
Order By: Relevance
“…The same study showed that the risk for ASD increases 5.75 times in fathers over 40, when comparing to those below 30 years of age, after controlling for year of birth, socioeconomic status and maternal age (25). Similar results were obtained in Iranian population, where again it was proven that ASD risk increases with paternal, but not maternal age (26). In several other studies, it was shown that ASD risk increases with paternal age (22)(23)(24)(25)(27)(28)(29) while in a study done in 2013, this was not confirmed (21).…”
Section: 1supporting
confidence: 59%
“…The same study showed that the risk for ASD increases 5.75 times in fathers over 40, when comparing to those below 30 years of age, after controlling for year of birth, socioeconomic status and maternal age (25). Similar results were obtained in Iranian population, where again it was proven that ASD risk increases with paternal, but not maternal age (26). In several other studies, it was shown that ASD risk increases with paternal age (22)(23)(24)(25)(27)(28)(29) while in a study done in 2013, this was not confirmed (21).…”
Section: 1supporting
confidence: 59%
“…Some studies found older maternal and paternal age to be independent risk factors for ASD [4][5][6][7]. Others found only maternal or paternal age to be a risk factor; [8][9][10][11][12] and some found an increased risk for ASD associated with advanced parental age in bivariate analyses but not after adjusting for covariates, such as psychopathology [13]. A possible role of parental age in ASD is of concern because trends in parental age at birth have been changing nationally; birth rates to women 35 years and older increased between 1990 and 2010 from 31.7 to 45.9 per 1,000 among 35-39 year old women, 6.1 to 10.2 per 1,000 among 40-44 year olds and 0.2 to 0.7 per 1,000 for 45-49 year old women [14].…”
Section: Introductionmentioning
confidence: 93%
“…Weighted odds ratios (ORs) and 95% CIs were calculated. Three sensitivity analyses were conducted including the removal of studies with (a) the largest magnitude of association; (b) that included autism and high rates of autism spectrum disorders (6,7,36); and (c), high rates of missing data on paternal age (6,8,13).…”
Section: Discussionmentioning
confidence: 99%